Cholesterol levels linked to abnormal plasma thiol concentrations and thiol/disulfide redox status in hyperlipidemic subjects - Kinscherf, Ralf; Cafaltzis, Konstantinos; Röder, Falk; Hildebrandt, Wulf; Edler, Lutz; Deigner, Hans-Peter; Breitkreutz, Raoul; Feussner, Giso; Kreuzer, Jörg; Werle, Egon; Michel, Gerd; Metz, Jürgen; et al. (Free radical biology and medicine, 2003)
Treatment of hyperlipidemic patients with the thiol compound N-acetylcysteine (NAC) was previously shown to cause a significant dose-related increase in the high-density lipoprotein (HDL)-cholesterol serum level, suggesting the possibility that its disease-related decrease may result from a diminished thiol concentration and/or thiol/disulfide redox status (REDST) in the plasma. We therefore investigated plasma thiol levels and REDST in normo-/hyperlipidemic subjects with and without coronary heart disease (CHD). The thiol level, REDST, and amino acid concentrations in the plasma and intracellular REDST of peripheral blood mononuclear cells (PBMC) have been determined in 62 normo- and hyperlipidemic subjects. Thirty-three of these subjects underwent coronary angiography, because of clinical symptoms of CHD. All groups of hyperlipidemic patients under test and those normolipidemic individuals with documented coronary stenoses showed a marked decrease in plasma thiol concentrations, plasma and intracellular REDST of PBMCs, and a marked increase in plasma taurine levels. Individual plasma thiol concentrations and plasma REDST were strongly negatively correlated with the serum LDL-cholesterol and positively correlated with the serum HDL-cholesterol level. Together with the earlier report about the effect of NAC on the HDL-cholesterol serum level, our findings suggest strongly that lower HDL-cholesterol serum levels may result from a decrease in plasma thiol level and/or REDST possibly through an excessive cysteine catabolism into taurine.
Gesehen am 19.10.2017